2016
DOI: 10.1021/acs.energyfuels.6b01324
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Spontaneous Imbibition in a Tight Reservoir with Nuclear Magnetic Resonance Testing

Abstract: Hydraulic fracturing is the significant technology for exploiting tight resources. Spontaneous water imbibition is an important mechanism governing the process of hydraulic fracturing, and the water imbibition from the fracture into the matrix is an essential factor that affects the reservoir production performance. In this study, imbibition experiments and nuclear magnetic resonance (NMR) testing were combined to analyze fluid flow tight core samples in a pore-scale level. The imbibition experiments were cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 51 publications
3
48
0
Order By: Relevance
“…Spontaneous imbibition is a very important mechanism of oil recovery from naturally fractured reservoirs and unconventional reservoirs (Lai et al, 2016;Teklu et al, 2017). When water is injected into reservoirs, it preferentially goes through the fracture system.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous imbibition is a very important mechanism of oil recovery from naturally fractured reservoirs and unconventional reservoirs (Lai et al, 2016;Teklu et al, 2017). When water is injected into reservoirs, it preferentially goes through the fracture system.…”
Section: Introductionmentioning
confidence: 99%
“…Combining C and T 2 spectrum, the pore-radius distribution, shown in Figure 3, is obtained. The relationship between T 2 , pore radius, and pore type is shown in Table 3 following the methods of Lai et al [36] and Liu et al [42].…”
Section: Pore Radius Distributionmentioning
confidence: 99%
“…Zhou et al [35] studied the influencing factors of SI, including rock size, rock properties, fluid properties, wettability, initial oil saturation, and boundary condition, by combining NMR and conventional SI experiments. Lai et al [36] demonstrated that the water is first imbibed into micropores and small mesopores, and variations in the T 2 spectrum are principally reflected in the T 2 stage when the relaxation time is ≥10 ms. Wang et al [37] reported oil contribution from micropores up to 53.34%, and that permeability of 0.1 mD is a critical point at which the oil contribution of mesopores surpasses that of micropores.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars also tried to obtain the relationship of pore radius distribution from transverse relaxation time (T 2 ) and from conventional mercury injection method considering these two methods can describe pore structures 28,29 . Meanwhile, assuming pore spaces can be simplified to be columnar or spherical, numerous studies gave a linear relation between T 2 and pore radius 3032 . Based on these technologies, scholars begin to use this technique to monitor water profile during imbibition in tight sandstone, shale or other unconventional rock samples 33 .…”
Section: Introductionmentioning
confidence: 99%